The bZIP Transcription Factor ZIP-11 Is Required for the Innate Immune Regulation in Caenorhabditis elegans - Zheng, Zhongfan; Aihemaiti, Yilixiati; Liu, Junqiang; Afridi, Muhammad Irfan; Yang, Shengmei; Zhang, Xiumei; Xu, Yongfu; Chen, Chunhong; Tu, Haijun (Frontiers in Immunology, 2021)
Innate immunity is the first line of host defense against pathogen infection in metazoans. However, the molecular mechanisms of the complex immune regulatory network are not fully understood. Based on a transcriptome profiling of the nematode Caenorhabditis elegans, we found that a bZIP transcription factor ZIP-11 was up-regulated upon infection by Pseudomonas aeruginosa PA14. The tissue specific RNAi knock-down and rescue data revealed that ZIP-11 acts in intestine to promote hose resistance against bacterial infection. We further showed that intestinal ZIP-11 regulates innate immune response through constituting a feedback loop with the conserved PMK-1/p38 mitogen-activated protein signaling pathway. Intriguingly, ZIP-11 interacts with a CCAAT/enhancer-binding protein, CEBP-2, to mediate the transcriptional response to P. aeruginosa PA14 infection independently of PMK-1/p38 pathway. In addition, human homolog ATF4 can functionally substitute for ZIP-11 in innate immune regulation of C. elegans. Our findings indicate that the ZIP-11/ATF4 genetic program activates local innate immune response through conserved PMK-1/p38 and CEBP-2/C/EBPγ immune signals in C. elegans, raising the possibility that a similar process may occur in other organisms.